2022
DOI: 10.3389/fbioe.2022.819716
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Vasomotion and Stochastic Resonance in Vasomotion

Abstract: Vasomotion is the spontaneous time-dependent contraction and relaxation of micro arteries and the oscillating frequency is about 0.01–0.1 Hz. The physiological mechanism of vasomotion has not been thoroughly understood. From the dynamics point of view, the heartbeat is the only external loading exerted on the vascular system. We speculate that the nonlinear vascular system and the variable period of the heartbeat might induce the low-frequency vasomotion. In this study, the laser Doppler flowmeter is used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…By using Fourier, Hilbert-Huang or wavelet transforms, several representative frequency ranges were found in skin LDF signals, including heartbeat (0.5-2 Hz), respiration (0.14-0.5 Hz), myogenic activity (0.05-0.14 Hz), neurogenic activity (0.02-0.05 Hz), and NO-mediated endothelial activity (0.0095-0.02 Hz). [9][10][11][12][13] Similar spectral characteristics of oscillations were also found in human skin temperature signals. 14,15 There is some evidence to support that the prevalence of vasomotion was altered in response to stimuli under pathological conditions, including arterial hypertension, peripheral arterial obstructive diseases (PAOD), chronic kidney disease (CKD), and diabetes.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…By using Fourier, Hilbert-Huang or wavelet transforms, several representative frequency ranges were found in skin LDF signals, including heartbeat (0.5-2 Hz), respiration (0.14-0.5 Hz), myogenic activity (0.05-0.14 Hz), neurogenic activity (0.02-0.05 Hz), and NO-mediated endothelial activity (0.0095-0.02 Hz). [9][10][11][12][13] Similar spectral characteristics of oscillations were also found in human skin temperature signals. 14,15 There is some evidence to support that the prevalence of vasomotion was altered in response to stimuli under pathological conditions, including arterial hypertension, peripheral arterial obstructive diseases (PAOD), chronic kidney disease (CKD), and diabetes.…”
Section: Introductionsupporting
confidence: 69%
“…In recent years, the PORH test with signal spectral analysis coupled, which quantified the periodic oscillations of flowmotion, provided new potential indicators specific to a certain physiological mechanism. By using Fourier, Hilbert‐Huang or wavelet transforms, several representative frequency ranges were found in skin LDF signals, including heartbeat (0.5–2 Hz), respiration (0.14–0.5 Hz), myogenic activity (0.05–0.14 Hz), neurogenic activity (0.02–0.05 Hz), and NO‐mediated endothelial activity (0.0095–0.02 Hz) 9–13 . Similar spectral characteristics of oscillations were also found in human skin temperature signals 14,15 .…”
Section: Introductionmentioning
confidence: 65%
“…We detected HDO in anesthetized rats. Several studies reported similar oscillatory signals in measurements sensitive to blood flow or arterial vessel diameter in various species such as mice (Drew et al, 2010;Mateo et al, 2017;Winder et al, 2017;Fan et al, 2020), rats (Fujii et al, 1990;Mayhew et al, 1996;Kleinfeld et al, 1998), rabbits (Hundley et al, 1988), cats (Rivadulla et al, 2011) and humans (Mitra et al, 1997;Obrig et al, 2000;Rayshubskiy et al, 2014;Liu et al, 2022), and identified vasomotion as their origin. Vasomotion refers to rhythmic oscillations of blood vessel diameter, which causes oscillations of blood flow (Aalkjaer et al, 2011).…”
Section: Vasomotion Leads To Hemodynamic Oscillationsmentioning
confidence: 87%
“…We intended to investigate the prevalence of these oscillations (referred as HDO) in fMRI data and identified oscillations with a frequency around 0.2 Hz in MED sedated animals. In contrast, studies applying other anesthesia or measuring awake subjects often reported a vasomotion frequency around 0.1 Hz (Fujii et al, 1990;Mayhew et al, 1996;Mitra et al, 1997;Kleinfeld et al, 1998;Obrig et al, 2000;Rivadulla et al, 2011;Rayshubskiy et al, 2014;Mateo et al, 2017;Fan et al, 2020;Liu et al, 2022). The higher oscillation frequency under MED sedation can be explained by the fact that MED is a vasoconstrictor (Sinclair, 2003;Fukuda et al, 2013) and vasoconstriction causes an increase in vasomotion frequency (Colantuoni et al, 1984;Fujii et al, 1990).…”
Section: Anesthesia Exerts Diverse Effects On Vasomotionmentioning
confidence: 99%